Level of Nursing Staff Education Related to Oral Care of Individuals in Home Care and Nursing Homes: an Integrative Review - Brito Reia, Verônica Caroline; Telles-Araujo, Gabriel de Toledo; Soares-Junior, Luiz Alberto Valente; Lins-Kusterer, Liliane; Caminha, Raquel D’Aquino Garcia; Silva Santos, Paulo Sérgio da (ARCHIVES OF HEALTH INVESTIGATION, 2025)
Background: The everyday practice of oral health care enables the process of understanding individuals' oral problems for health promotion and prevention in deshospitalized older people. The nursing staff could they act as valuable and productive partner in oral health, helping patients with home care. The dentist can assist in maintaining this dental hygiene by emphasizing thorough and continuous follow-up care. Objective: The objective of this review was to search for scientific evidence on the level of education and knowledge of the nursing staff working in home care and/or in nursing homes in oral health care of individuals under long-stay care. Methods: The PRISMA-ScR recommendations were followed in conducting this integrative review. The research question was applied in the electronic databases PubMed, LILACS, Embase, and Web of Science using the necessary keywords and Medical Subject Heading terms. The studies were allocated to the reference management software EndNote Web, in which five published articles were selected for the narrative synthesis of data. Results: The final sample included 5 selected articles with a total of 392 nursing staff responded to the pre-set questionnaires about their level of education and knowledge about the oral health care of individuals. Dental hygienists were the specialists in charge of supervising dental care and teaching the nursing personnel. As a means of educating the oral care team, health education programs were developed. Conclusion: Dentists must be an integral part of the multidisciplinary team responsible for the patient and play a key role in guiding the nursing team.